Rekonstruksi Legitimasi Koperasi: Krisis Identitas Koperasi Desa Merah Putih - Tika Diliana (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study critically evaluates the legitimacy and cooperative identity of the Koperasi Desa Merah Putih (Kopdes MP), a state-initiated cooperative program mandated by Presidential Instruction No. 9 of 2025. Despite its wide-scale implementation, concerns persist regarding its alignment with international cooperative principles. Using a Systematic Literature Review (SLR) method and Levi's (1994) typology framework, this research examines whether Kopdes MP reflects genuine cooperative characteristics or functions as a pseudo cooperative. Findings indicate that while Kopdes MP fulfills legal formalities, it often lacks voluntary membership, democratic governance, member economic participation, and educational engagement—core cooperative principles defined by the International Cooperative Alliance (ICA). The study reveals that Kopdes MP occupies a structural space between pseudo and self-centered cooperatives, driven by top-down policies rather than community initiative. It concludes by proposing a diagnostic framework to assess cooperative authenticity, offering theoretical and policy contributions to the field of cooperative development in Indonesia and beyond. Keywords: cooperative identity, pseudo cooperative, Kopdes Merah Putih, Levi typology, cooperative governance, state-driven cooperatives